Pertumbuhan Stek Batang Dua Jenis Buah Naga dan Pemberian Pupuk NPK Majemuk - Sukma Dewi; Husna Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is to figure out the interaction influences of two species of dragon fruit seedlings and the application of compound NPK fertilizer, and to determinate the best fertilizer dosage for dragon fruit seedling growth. This research had implemented in Screen Home Experimentation Faculty Agriculture, University of Riau on November of 2015 until February 2016 by station factorial design which is arranged in Randomized Block Design (RAK) and consists of two factors. The first factor is the species of dragon fruits (N); red and white. The second factor is the giving of compound NPK fertilizer, they are 1 g, 2 g, 3 g, 4 g and 5 g. Data obtained of the research, analyzed with variance and Honestly Significant Difference (BNJ) on 5%. Results of the research suggest that the interacton between two species of dragon fruit seedlings and the suggest of NPK fertilizer there is no significant difference on budding, the number and the length of budding, the number and the length of roots, the volume of roots, the fresh and dry weight of budding. The application of compound NPK fertilizer there is no significant difference in all of observatios. Based on is the researchs of stem cutting growth of two species of dragon fruit seedlings is recommended to give 1 g/ 3 kg soilof compound NPK fertilizer.Keywords: dragon fruit, compound